Modelling Land use Patterns of Lahore (Pakistan) using Remote Sensing and GIS (Global Journal of Science Frontier Research, 2014)
In this research, an attempt was made to reveal the land use patterns of Lahore, the 2nd largest city of Pakistan, using remote sensing and GIS techniques. Results revealed that at present more than 1200 hectares of agricultural and forest land is acquired for urban uses every year. From 1972 to 2009, the urban area of Lahore expanded 68 percent while a loss of 32500 hectares in agricultural land is recorded. Around 5000 hectares of forest land had vanished from the landscape of the city. More than 200 rural localities have been merged into the city since 1972. Around 100 new housing schemes are approved to accommodate the ever increasing population at the expense of loss in agricultural land. Most of the expansion took place in south and southwest direction along major roads and highways.
Keywords: land use; remote sensing; GIS; lahore